Peningkatan Kompetensi Guru Melalui Pelatihan Penggunaan Teknologi AI (GPT) dalam Pengembangan Bahan Ajar Digital - Fitriana Harahap; Husin Sariangsah; Hanafi Asnan; Masri Wahyuni; Joko Eriyanto (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program was carried out with the aim of enhancing teachers’ competencies in utilizing Artificial Intelligence technology, particularly the Generative Pre-trained Transformer (GPT), as a tool for developing digital teaching materials. The background of this activity stems from the limited understanding of teachers in applying AI technology to support 21 st-century learning. The implementation method involved intensive training that included an introduction to GPT concepts, hands-on practice in creating digital modules, designing evaluation questions, and simulating the use of teaching materials in the classroom. The activity was attended by several teachers from SMP Zawiyyah Darussalami, who demonstrated high enthusiasm throughout the sessions. Evaluation through pre-test and post-test results showed a significant improvement in teachers’ understanding and skills in using GPT. Thus, this community service activity successfully provided a positive impact by improving teachers’ competencies and opening opportunities for GPT utilization as an innovation in digital learning within schools.